Vessel and sex differences in pericoronary adipose tissue attenuation obtained with coronary CT in individuals without coronary atherosclerosis - van Rosendael Sophie E; Kuneman Jurrien H; van den Hoogen Inge J; Kitslaar Pieter H; van Rosendael Alexander R; van der Bijl Pieter; Reiber Johan H. C; Marsan Nina Ajmone; Jukema J. Wouter; Knuuti Juhani; Bax Jeroen J. (SPRINGER, 2022)
Pericoronary adipose tissue (PCAT) attenuation, derived from coronary computed tomography angiography (CCTA), is associated with coronary artery inflammation. Values for PCAT attenuation in men and women without atherosclerosis on CCTA are lacking. The aim of the current study was to assess the mean PCAT attenuation in individuals without coronary artery atherosclerosis on CCTA. Data on PCAT attenuation in men and women without coronary artery atherosclerosis on CCTA were included in this retrospective analysis. The PCAT attenuation was analyzed from the proximal part of the right coronary artery (RCA), the left anterior descending artery (LAD), and the left circumflex artery (LCx). For patient level analyses the mean PCAT attenuation was defined as the mean of the three coronary arteries. In 109 individuals (mean age 45 +/- 13 years; 44% men), 320 coronary arteries were analyzed. The mean PCAT attenuation of the overall population was - 64.4 +/- 8.0 HU. The mean PCAT attenuation was significantly lower in the LAD compared with the LCx and RCA (- 67.8 +/- 7.8 HU vs - 62.6 +/- 6.8 HU vs - 63.6 +/- 7.9 HU, respectively, p < 0.001). In addition, the mean PCAT attenuation was significantly higher in men vs. women in all three coronary arteries (LAD: - 65.7 +/- 7.6 HU vs - 69.4 +/- 7.6 HU, p = 0.014; LCx: - 60.6 +/- 7.4 HU vs - 64.3 +/- 5.9 HU, p = 0.008; RCA: -61.7 +/- 7.9 HU vs - 65.0 +/- 7.7 HU, p = 0.029, respectively). The current study provides mean PCAT attenuation values, derived from individuals without CAD. Moreover, the mean PCAT attenuation is lower in women vs. men. Furthermore, the mean PCAT attenuation is significantly lower in the LAD vs LCx and RCA.